Does location matter? A proposed methodology to evaluate neighbourhood effects on cardiac arrest survival and bystander CPR. Issue 3 (3rd March 2015) - Buick, Jason E.; Allan, Katherine S.; Ray, Joel G.; Kiss, Alexander; Dorian, Paul; Gozdyra, Peter; Morrison, Laurie J.
Abstract: Background: Traditional variables used to explain survival following out-of-hospital cardiac arrest (OHCA) account for only 72% of survival, suggesting that other unknown factors may influence outcomes. Research on other diseases suggests that neighbourhood factors may partly determine health outcomes. Yet, this approach has rarely been used for OHCA. This work outlines a methodology to investigate multiple neighbourhood factors as determinants of OHCA outcomes. Methods: A retrospective, observational cohort study design will be used. All adult non-emergency medical service witnessed OHCAs of cardiac etiology within the city of Toronto between 2006 and 2010 will be included. Event details will be extracted from the Toronto site of the Resuscitation Outcomes Consortium Epistry—Cardiac Arrest, an existing population-based dataset of consecutive OHCA patients. Geographic information systems technology will be used to assign patients to census tracts. Neighbourhood variables to be explored include the Ontario Marginalization Index (deprivation, dependency, ethnicity, and instability), crime rate, and density of family physicians. Hierarchical logistic regression analysis will be used to explore the association between neighbourhood characteristics and 1) survival-to-hospital discharge, 2) return-of-spontaneous circulation at hospital arrival, and 3) provision of bystander cardiopulmonary resuscitation (CPR). Receiver operating characteristics curves will evaluate each model's ability to discriminate between those with and without each outcome. Discussion: This study will determine the role of neighbourhood characteristics in OHCA and their association with clinical outcomes. The results can be used as the basis to focus on specific neighbourhoods for facilitating educational interventions, CPR awareness programs, and higher utilization of automatic defibrillation devices. RÉSUMÉ: Contexte: Les variables classiques ne permettent d'expliquer que 72 % de la survie des malades à la suite d'un arrêt cardiaque extrahospitalier (ACEH), ce qui donne à penser que d'autres facteurs inconnus peuvent influer sur les résultats. Des recherches sur d'autres maladies semblent indiquer que des facteurs relatifs aux quartiers peuvent déterminer en partie les résultats cliniques. Pourtant, ce type de recherche a rarement été appliqué au contexte des ACEH. Sera exposée ici une méthode visant à étudier différents facteurs relatifs aux quartiers et à les considérer comme des déterminants de résultats cliniques après un ACEH. Méthode: Pour ce faire, nous avons mené une étude de cohortes, rétrospective et observationnelle. Ont été retenus tous les adultes non rattachés à des services médicaux d'urgence, témoins d'un ACEH d'origine cardiaque, survenu dans la ville de Toronto entre 2006 et 2010. Les renseignements sur les faits ont été tirés du site Resuscitation Outcomes Consortium Epistry – Cardiac Arrest, une base de données déjà existante, située à Toronto, fondée sur une population composée de malades consécutifs ayant subi un ACEH. Pour ce qui est de la localisation, des systèmes d'information géographique ont été utilisés pour lier les malades à des secteurs de recensement. Les variables relatives aux quartiers devant être examinées comprenaient l'Ontario Marginalization Index (indice de marginalisation de l'Ontario; privations, dépendance, origine ethnique et instabilité), le taux de criminalité et la densité des omnipraticiens. Une analyse de régression logistique hiérarchique a servi à étudier l'association entre les caractéristiques des quartiers et 1) la survie jusqu'au congé de l'hôpital; 2) le rétablissement spontané de la circulation sanguine à l'arrivée à l'hôpital; et 3) les manœuvres de réanimation cardiorespiratoire (RCR) appliquées par les passants. Des courbes caractéristiques de la performance des tests ont permis d'évaluer la capacité du modèle à discerner les variables qui comportaient ou non l'un ou l'autre des résultats d'intérêt. Discussion: L'étude permettra de déterminer le rôle des quartiers dans le contexte des ACEH et d'établir des associations avec les résultats cliniques. Les faits dégagés pourront servir de base à la caractérisation des quartiers afin de faciliter les interventions éducatives, la mise en œuvre des programmes de sensibilisation à la RCR et l'utilisation accrue des appareils de défibrillation automatique.